(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Background: Viral hepatitis is an infection of the liver caused by one of several viruses. In the United States, the most common types of viral hepatitis are Hepatitis A, Hepatitis B, and Hepatitis C. While all three types of hepatitis can cause similar symptoms, each virus is spread in different ways. Objectives: The study aims at identifying the Sociodemographic characteristics to sample. And evaluating teacher’ knowledge about the early detection of Hepatitis (A) diseases at primary schools in Al-Hilla city. Methodology: A descriptive study was conducted, included (181) primary school, (30) in urban and rural area of primary schools in AL- Hilla city, December 1th 2019 to February 16th 2020, evaluating teacher’ knowledge about the early detection of Hepatitis (A) diseases. A probability (purposive sample) of sample of 60 teachers who were attending urban and rural area of primary schools. The data were collected through the utilization of the developed questionnaire after the validity and reliability are estimated, and by means of interview technique. Reliability of the questionnaire is determined through a pilot study and the validity through (16) experts. The data analyzed through the use of the descriptive and inferential statistical analysis procedures. Results: The findings of the present study indicate that the overall evaluation of teachers’ knowledge about the early detection for Hepatitis (A) diseases was poor. Conclusions: The study conclude if that lack of teacher ‘s knowledge about early detection of Hepatitis (A) diseases in general in regard to common childhood communicable diseases. Recommendations: The study recommended the needs to teachers that everyone is responsible for prevention of the spread of a communicable disease such as oneself, parents, schools, community members, etc.